2016
DOI: 10.1016/j.fertnstert.2015.10.036
|View full text |Cite
|
Sign up to set email alerts
|

Assessing new terminal body and facial hair growth during pregnancy: toward developing a simplified visual scoring system for hirsutism

Abstract: ChiCTR-OCH-14005012.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…However, the complex changes seen in pregnancy (including increases in human chorionic gonadotropin, progesterone, prolactin, numerous growth factors, and cytokines) may well contribute to the increase in the rate of hair growth, in the hair diameter, and in the anagen/telogen ratio observed in pregnant women [ 63 , 64 , 65 ]. Hormonal changes due to gestation may cause some new terminal hair growth mainly at the abdomen, the lower back, and the thighs [ 66 ]. Sudden and severe hirsutism and/or acne during pregnancy may be a symptom of malignant ovarian or adrenal conditions, such as luteomas or Cushing’s syndrome [ 67 , 68 , 69 ].…”
Section: Hormonal Effects On Hair At Different Stages Of the Life mentioning
confidence: 99%
“…However, the complex changes seen in pregnancy (including increases in human chorionic gonadotropin, progesterone, prolactin, numerous growth factors, and cytokines) may well contribute to the increase in the rate of hair growth, in the hair diameter, and in the anagen/telogen ratio observed in pregnant women [ 63 , 64 , 65 ]. Hormonal changes due to gestation may cause some new terminal hair growth mainly at the abdomen, the lower back, and the thighs [ 66 ]. Sudden and severe hirsutism and/or acne during pregnancy may be a symptom of malignant ovarian or adrenal conditions, such as luteomas or Cushing’s syndrome [ 67 , 68 , 69 ].…”
Section: Hormonal Effects On Hair At Different Stages Of the Life mentioning
confidence: 99%
“…Although serum glucose was slightly increased, which is in part owing to younger age, the dynamic insulin responses in the HT‐LCMS subgroup showed dramatic changes compared with those in the NT‐LCMS subgroup. In addition, the PCOS patients with IR defined by HIN, HOMA‐IR, and IFG also showed a high incidence of hirsutism (Figure ), the clinical HA diagnosed on the basis of a specific cut‐off value of mFG …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the PCOS patients with IR defined by HIN, HOMA-IR, and IFG also showed a high incidence of hirsutism (Figure 2), the clinical HA diagnosed on the basis of a specific cut-off value of mFG. 10,14 In vitro studies have shown that insulin can directly stimulate ovarian steroidogenesis and/or augment luteinizing hormone (LH)-stimulated androgen secretion or indirectly enhance the amplitude of gonadotropin-releasing hormone (GnRH)-stimulated LH pulses. According to the literature, lowering insulin levels with insulin-sensitizing drugs, such as metformin and thiazolidinediones, can reduce circulating androgen levels or the bioactivity of testosterone and increase sex hormone binding globulin (SHBG) levels.…”
Section: Discussionmentioning
confidence: 99%
“…The subjects were divided into two groups of 30 PCOS women and 30 normal women, respectively, who were between 25 and 40 years old. The inclusion criteria were infertile PCOS women who met 2 of the 3 Rotterdam criteria: (12)(13)(14) 1) oligo-ovulation or anovulation defined as <8 menstrual cycles in the past year, 2) hyperandrogenism (hirsutism or acne), with hirsutism defined by a Ferriman-Gallwey (FG) self-reported score of >5 (for Asian), 3) polycystic ovaries (PCO) as detected by transvaginal ultrasound (TVUS) with 12 follicles of 2-9 mm diameter, and age 23-40 years. The controls were 30 normal women who were undergoing sterilization and/or routine VIA (visual inspection with acetic acid) screening, history taking and gynecological examinations, and not suspected of suffering from PCOS (no pelvic pain, no history of dysmenorrhea or dyspareunia, normal clinical gynecological examination).…”
Section: Research Subjectsmentioning
confidence: 99%